Changing tires on a moving car: the role of timing in hospitality and service turnaround processes. (January 2019) - Schmitt, Achim; Raub, Steffen; Schmid, Simon; Rudie Harrigan, Kathryn
Highlights: Timing of retrenchment and recovery activities is of key importance for turnarounds. An exclusive focus on retrenchment is not suitable for service and hospitality environments. Retrenchment and recovery activities interact to predict service turnaround performance. Hospitality turnarounds are characterized by a simultaneous retrenchment and recovery process. Abstract: Corporate turnaround processes consist of two main strategies: retrenchment and recovery. Whereas retrenchment focuses on efficiency and cost reduction, recovery entails strategic repositioning for long-term growth. Prior research has emphasized the timing of turnaround strategies as critical for the overall turnaround success and proposed a sequential or simultaneous timing of retrenchment and recovery. However, a sequential timing of turnaround strategies may have important disadvantages in the particular context of the service sector, given that it may quickly lead to staff demotivation, declining service quality and loss of customers. This research investigates the timing of retrenchment and recovery activities in service industry turnarounds with a multi-method approach. 35 service industry turnarounds in the German-speaking markets of Western Europe (Austria, Germany, and Switzerland) were analyzed. Based on the results of the first study, the research was complemented with a qualitative study of six turnaround cases in the Swiss hospitality industry. The converging evidence from both studies suggests that retrenchment and recovery activities interact in predicting the performance of service turnarounds. This suggests that a simultaneous turnaround process provides a more adequate timing for turnarounds in the specific service environment. The findings have important implications for turnaround theory and for managerial practice in service turnarounds.